Medical Record Management Analysis Of Inpatient Patients Based On Standards Of Medical Record Services In Government Hospital In Medan - Hasan Basri Nasution, Muhammad; Girsang, Ermi; Eliza Putri Lubis, Yolanda; Napiah Nasution, Ali (International Journal of Health and Pharmaceutical (IJHP), 2022)
Inpatient medical records have an important role as a source of data and health information for inpatients related to treatment and care planning. The main factor that causes problems in inpatient medical records is the undisciplined factor of the person in charge who handles patients in filling out medical records. This can cause inpatient medical record management, not in accordance with medical record service standards. This study aimed to analyze inpatient medical record management based on medical record service standards. This research is a quantitative analytic study with a cross-sectional approach. The study was conducted at the Government Hospital in Medan. The research population was 126 people and all of them were used as samples. Sampling by means of total sampling. Data analysis used univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level (0.05). The results showed that inpatient medical record management implementation based on medical record service standards at the Government Hospital in Medan was influenced by work motivation (p = 0.001) and supervision (p = 0.000). While the variables that have no effect are length of work (p = 1,000), education (p = 0.848), teamwork (p = 0.241), and completeness of infrastructure (p = 0.760). The supervision variable is the most dominant variable or has the greatest influence with the value of Exp(B)/OR = 19,542. Medical record employees who state that supervision is carried out well by superiors will improve the implementation of inpatient medical record management well, compared to those who state that supervision is still not good. It is recommended that the leadership carry out inherent supervision (waskat) to all medical record employees and provide motivation through motivational seminars to improve the implementation of inpatient medical record management based on medical record service standards.